2013
DOI: 10.1039/c3cp53760a
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic increase of oxygen reduction favourable Fe–N coordination structures in a ternary hybrid of carbon nanospheres/carbon nanotubes/graphene sheets

Abstract: A Fe/N co-doped ternary nanocarbon hybrid, with uniform bamboo-like carbon nanotubes (CNTs) in situ grown on/between the single/few-layer graphene sheets interspaced by carbon nanosphere aggregates, was prepared through a one-pot heat treatment of a precursor mixture containing graphene oxide, Vulcan XC-72 carbon nanospheres, nitrogen rich melamine and small amounts of Fe ions. Physical characterization including electron microscopic images, N2 adsorption-desorption isotherms, pore size distribution, XPS, XRD,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 39 publications
(104 reference statements)
0
28
0
Order By: Relevance
“…Precious works reported two different models to describe the active sites in M-N/C catalyst for ORR. One is the M-N x species, 27,29,47 and the other is the doping N atoms in the carbon surface. [48][49][50] In our control experiment (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Precious works reported two different models to describe the active sites in M-N/C catalyst for ORR. One is the M-N x species, 27,29,47 and the other is the doping N atoms in the carbon surface. [48][49][50] In our control experiment (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…16c produced a measured area current activity of 9.9 mA cm −2 at 0.9 V iR-free and a peak power density of 0.9 W cm −2 . Other framework substrate methods, such as a combination of various carbon materials [164][165][166] and synthesis with silica template [131,167,168] or NaCl template [169], were also found to create abundant channels/pores to facilitate mass transportation.…”
Section: Mass Transportationmentioning
confidence: 99%
“…The multi-technique characterization have suggested that the enviable performance should be ascribed to the formation of metal-N complexion structures as well as the carbon nanostructures such as thin graphene sheets and nanofibers [10][11][12]. It has been generally accepted that the formation of uniform and ordered carbon nanostructures is very important in enhancing the catalytic activity [10][11][12][13][14][15][16][17][18][19].…”
Section: Open Accessmentioning
confidence: 99%
“…We also prepared the composite of PANIs with graphene nanosheets (GS) that were prepared by high temperature thermal reduction of graphene oxide [17,18]. In this case, 30 mg of GS were added into the CTAB solution to prepare the PANI, which corresponded to a PANI/GS ratio of 1/8.…”
Section: Materials Synthesismentioning
confidence: 99%